Prediction of potential climate change impacts on the geographic distribution shift of Selaginella kraussiana and S. uncinata in East, South and Southeast Asia - AHMAD DWI SETYAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; ILYAS NURSAMSI; MUHAMMAD NUR SULTON; GILANG DWI NUGROHO (Smujo International, 2026)
Abstract. Setyawan AD, Sutarno, Sugiyarto, Sunarto, Nursamsi I, Sulton MN, Nugroho GD. 2026. Prediction of potential climate change impacts on the geographic distribution shift of Selaginella kraussiana and S. uncinata in East, South and Southeast Asia. Nusantara Bioscience 18 (1): n180105. https://doi.org/10.13057/nusbiosci/n180105. Climate change is increasingly altering the geographic distribution of invasive plant species, yet comparative assessments of closely related invasive taxa remain limited. This study evaluated the potential impacts of climate change on the future distribution of two invasive lycophytes, Selaginella kraussiana and S. uncinata, across East, South, and Southeast Asia. Species distribution models were developed using the Maximum Entropy (MaxEnt) algorithm based on occurrence records compiled from GBIF, field observations, and published literature. The models incorporated 15 environmental variables representing bioclimatic, edaphic, UVB-radiation, and topographic factors. Future habitat suitability was projected for 2030, 2050, and 2080 under four Representative Concentration Pathway (RCP) scenarios (2.6, 4.5, 6.0, and 8.5). Model performance was high for both species, with AUC values of 0.935 for S. kraussiana and 0.966 for S. uncinata, indicating excellent predictive accuracy. Environmental controls differed markedly between the species. Selaginella kraussiana was primarily associated with temperature-related variables, particularly the minimum temperature of the coldest month (bio_6), whereas S. uncinata was more strongly associated with annual precipitation (bio_12) and other moisture-related variables. Future projections indicated substantial habitat expansion for S. kraussiana, with total suitable habitat increasing from 11.47 × 10⁶ km² under current conditions to 16.43 × 10⁶ km² under RCP 8.5 by 2080. Expansion was projected mainly into higher-latitude and higher-elevation subtropical and temperate regions. In contrast, S. uncinata exhibited relatively stable distribution patterns, with total suitable habitat changing only slightly from 2.95 × 10⁶ km² to 3.04 × 10⁶ km² across future climate scenarios. These findings suggest that S. kraussiana may experience a greater climate-driven increase in invasion potential than S. uncinata and demonstrate the value of integrating species distribution modeling with ecological interpretation to support invasion-risk assessment, early detection, and climate-adaptive management of invasive lycophytes in Asia.